Enhancing Hydrogen Diffusion in Silica Matrix by Using Metal Ion Implantation to Improve the Emission Properties of Silicon Nanocrystals - J. Bornacelli; J. A. Reyes-Esqueda; L. Rodríguez-Fernández; J. L. Ruvalcaba-Sil; F. J. Jaimes; A. Oliver (Journal of Nanotechnology)
Efficient silicon-based light emitters continue to be a challenge. A great effort has been made in photonics to modify silicon in order to enhance its light emission properties. In this aspect silicon nanocrystals (Si-NCs) have become the main building block of silicon photonic (modulators, waveguide, source, and detectors). In this work, we present an approach based on implantation of Ag (or Au) ions and a proper thermal annealing in order to improve the photoluminescence (PL) emission of Si-NCs embedded in SiO2. The Si-NCs are obtained by ion implantation at MeV energy and nucleated at high depth into the silica matrix (1-2 μm under surface). Once Si-NCs are formed inside the SiO2 we implant metal ions at energies that do not damage the Si-NCs. We have observed by, PL and time-resolved PL, that ion metal implantation and a subsequent thermal annealing in a hydrogen-containing atmosphere could significantly increase the emission properties of Si-NCs. Elastic Recoil Detection measurements show that the samples with an enhanced luminescence emission present a higher hydrogen concentration. This suggests that ion metal implantation enhances the hydrogen diffusion into silica matrix allowing a better passivation of surface defects on Si NCs.